2017
DOI: 10.1002/jssc.201601102
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes-A resin for electrochemically modulated liquid chromatography

Abstract: Electrochemically modulated liquid chromatography is a special form of ion exchange chromatography in which the separation process is controlled by applying an electric potential to the stationary phase. This form of chromatography has so far only been applied in research studies. The present study shows that multiwalled carbon nanotubes are an effective resin material for an electrochemically modulated chromatography process. The experiments are carried out in a newly designed column that enables the packing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The work presented here was carried out entirely in a self-designed PCC column based on the example of Brammen et al [28]. As stationary phase material, MWCNTs (CNT-K, Future Carbon GmbH, 95448 Bayreuth, Germany) with an outer diameter of 20-40 nm and a density of 2.1 g/cm 3 were packed in a curled, strong cation exchange membrane (CMI-7000, Membranes International Inc., Ringwood, NJ 07456, USA).…”
Section: Materials and Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…The work presented here was carried out entirely in a self-designed PCC column based on the example of Brammen et al [28]. As stationary phase material, MWCNTs (CNT-K, Future Carbon GmbH, 95448 Bayreuth, Germany) with an outer diameter of 20-40 nm and a density of 2.1 g/cm 3 were packed in a curled, strong cation exchange membrane (CMI-7000, Membranes International Inc., Ringwood, NJ 07456, USA).…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…Brammen et al [28] developed a three-electrode column setup, with a bed volume of approximately 10 mL, and used Baytubes C150P carbon nanotubes as a stationary phase material. They confirmed that these MWCNTs, with excellent electrical, chemical and mechanical properties, are suitable and offer decisive advantages for PCC.…”
Section: The Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CNTs can be employed as hydrophobic interaction chromatography (HIC) resin which was demonstrated by Biesaga and Pyrzynska who were able to purify dicamba herbicides by the use of CNTs as chromatography resin [11]. For electrochemically modulated chromatography applications and the control of ion exchange by a potential switch, CNTs represent a very promising stationary phase material [12,13]. Furthermore, an application as extraction material for nonpolar compounds has been demonstrated [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the search for new natural radical-scavenging reactive molecule, complex mixtures interferences are frequently encountered. The developed methods involving free radical reactive molecule assays coupled with HPLC were successfully developed [11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%